Enhancing the antibacterial ability of Ligilactobacillus salivarius through ARTP mutagenesis breeding: an effective strategy to improve its probiotic properties - Zhou, Hetian; Du, Yunping; Yu, Guolian; Liu, Wei; Zeng, Juanjuan; Wang, Bin; Chen, Maojin; Wang, Yujue; Zhang, Wenbo; Wei, Xiaona (Frontiers in Microbiology, 2025)
IntroductionLigilactobacillus salivarius (L. salivarius), a well-characterized probiotic species with established safety and functional efficacy, has been widely applied in poultry production for decades. Its probiotic attributes primarily encompass inhibiting pathogenic bacterial proliferation, regulating host intestinal microbiota, and modulating immune responses to enhance animal health. Given the substantial variability in biological and probiotic characteristics among different L. salivarius strains, identifying optimal strains with enhanced probiotic efficacy typically requires extensive in vivo evaluations.MethodsIn this study, we employed atmospheric and room temperature plasma (ARTP) mutagenesis to improve the antibacterial activity of the isolated D428 strain. Following ARTP mutagenesis and positively screened for its antibacterial ability, the mutant strain 30s-37 was obtained. By comparing the effects of the parental (D428) and mutant (30s-37) strains on broiler growth performance and intestinal microbiota, their probiotic properties performance was evaluated.ResultsThe results indicated that the use of L. salivarius strains improved the growth performance and increased the richness and diversity of cecal probiotic microbial communities, with the mutagenized strain 30s-37 exhibiting more pronounced effects.DiscussionThese findings underscore mutagenesis breeding as an effective strategy for probiotic strain optimization, justifying its expanded application in future strain development programs.